Micro-bottle resonator for liquid ethanol and sodium hypochlorite sensing / Nurul Atika Baharuddin - Nurul Atikah, Baharudddin (2022)
Optical micro-bottle resonator (MBR) structure fabricated based on arc fusion approach was widely deployed to implement highly compact, low cost and versatile sensor device. This dissertation presents an investigation on MBR for liquid ethanol and sodium hypochlorite sensing. The resonator was made of an SMF-28 silica fiber using a new method known as “soften-and-compress” to create a bottle structure. At first, the MBR with a midriff diameter